2009
DOI: 10.1016/j.cellsig.2009.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Integrated modulation of phorbol ester-induced Raf activation in EL4 lymphoma cells

Abstract: The EL4 murine lymphoma cell line exists in variant phenotypes that differ with respect to responses to the tumor promoter phorbol 12-myristate 13-acetate (PMA1). Previous work showed that “PMA-sensitive” cells, characterized by a high magnitude of PMA-induced Erk activation, express RasGRP, a phorbol ester receptor that directly activates Ras. In “PMA-resistant” and “intermediate” EL4 cell lines, PMA induces Erk activation to lesser extents, but with a greater response in intermediate cells. In the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…We also found that blocking Akt by curcumin remarkably decreased the levels of phospho-Bad, phospho-GSK-3β, phospho-c-Raf and pro-caspase-9 in EJ cells, indicating an increasing activity of Bad, GSK-3β, c-Raf and caspase-9. Although c-Raf was activated by curcumin in EJ cells, it is unknown whether sufficient activation of c-Raf activates the Raf/Erk cascades, because c-Raf activity is also regulated by protein-protein interaction [ 60 ], further research will be required. Accordingly, the suppression of anti-apoptotic PI3K/Akt signaling pathway by curcumin is also an important mechanism of action in c-myc-induced EJ cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that blocking Akt by curcumin remarkably decreased the levels of phospho-Bad, phospho-GSK-3β, phospho-c-Raf and pro-caspase-9 in EJ cells, indicating an increasing activity of Bad, GSK-3β, c-Raf and caspase-9. Although c-Raf was activated by curcumin in EJ cells, it is unknown whether sufficient activation of c-Raf activates the Raf/Erk cascades, because c-Raf activity is also regulated by protein-protein interaction [ 60 ], further research will be required. Accordingly, the suppression of anti-apoptotic PI3K/Akt signaling pathway by curcumin is also an important mechanism of action in c-myc-induced EJ cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Dual phosphorylation of a specific SPKTP motif within BRAF and CRAF was shown to down-regulate ERK1/2 activation, [76], with phosphorylation of BRAF residues S750 and T753 impairing BRAF:CRAF dimerisation and reducing ERK1/2 activation [77]. Additionally, phosphorylation of S289, S296 and S301 of CRAF by ERK1/2 has also been shown to inactivate RAF signalling [78]. ERK1/2-dependent BRAF phosphorylation reduces heterodimer formation due to reduced affinity for RAS ( phosphorylation at S151) and direct disruption of BRAF:CRAF heterodimers ( pT401, pS750 and pT753) [79] As ERK1/2 feedback phosphorylation impairs RAF dimerisation it is effective at blocking wild-type RAF activity.…”
Section: Erk1/2-mediated Feedback Inhibition Regulates Raf Dimerisationmentioning
confidence: 99%
“…Thus, PKC-dependent phosphorylation of AC-C1 domain induces AC activation (Ebina et al, 1997 ). However, one must be cautious on the use of PMA as a specific AC-activator since PMA has also been reported to have actions on non-kinase proteins including chimaerins, RasGRP, and Unc-13/Munc-13 (Han and Meier, 2009 ; Kazanietz et al, 1995 ).…”
Section: Modulation Of Camp Concentration In the Cardiac Tissuementioning
confidence: 99%